Parkinson's Disease Sleep Scale-2: The Brazilian Version's Cross-Cultural Adaptation and Validation - Rogério José de Souza; Amanda dos Santos Siqueira; Luísa Vigiani Cassiano; Tais Caroline Oliveira da Silva; Suhaila Mahmoud Smaili (Sleep Science)
Objective To translate, cross-culturally adapt, and validate the Brazilian version of the Parkinson's Disease Sleep Scale-2 (PDSS-2/BR).